Loyalitas Pelanggan Dipengaruhi oleh Kualitas Layanan Melalui Kepuasan Pelanggan Salon the Guh di Plaza Cibubur Bekasi - Yunna Wijaya; Eddy Sanusi Silitonga (Jurnal Manajemen Bisnis Krisnadwipayana, 2025)
This study aims to determine customer loyalty influenced by service quality through customer satisfaction The Guh Salon in Plaza Cibubur Bekasi. The research method used is a quantitative approach. The sample used in this study consumers who used The Guh Salon services, with data collected using questionnaires. The collected data was analyzed using path analysis. The results of the study indicate that 1) Service quality has a positive and significant effect on customer loyalty; 2) Customer satisfaction has a positive and significant effect on customer loyalty; 3) Service quality has a positive and significant effect on customer satisfaction; 4) Customer loyalty is influenced by service quality through customer satisfaction.